COMPARATIVE STUDY OF PERIODIC AND CUMULATIVE CONSTRUCTIONS - Xamrayeva Zebiniso Xaydarovna; Dinara Turgunbaevna Teshebayeva (Journals Park Publishing, 2025)
Periodic and cumulative constructions represent two fundamental syntactic structures used in written and spoken discourse. While periodic sentences delay the main idea until the end, creating suspense and emphasis, cumulative sentences begin with the main clause and then add descriptive elements. This study researches their structural differences, rhetorical significance, and literary applications. By analyzing examples from classical and modern literature, this paper demonstrates how these constructions shape meaning, enhance expressiveness, and influence reader perception.
Keywords: Periodic sentence, cumulative sentence, syntactic construction, rhetoric, literature, structure, emphasis.